Photodynamic Therapy—Current Limitations and Novel Approaches - Gunaydin, Gurcan; Gedik, M. Emre; Ayan, Seylan (Frontiers in Chemistry, 2021)
Photodynamic therapy (PDT) mostly relies on the generation of singlet oxygen, via the excitation of a photosensitizer, so that target tumor cells can be destroyed. PDT can be applied in the settings of several malignant diseases. In fact, the earliest preclinical applications date back to 1900s. Dougherty reported the treatment of skin tumors by PDT in 1978. Several further studies around 1980 demonstrated the effectiveness of PDT. Thus, the technique has attracted the attention of numerous researchers since then. Hematoporphyrin derivative received the FDA approval as a clinical application of PDT in 1995. We have indeed witnessed a considerable progress in the field over the last century. Given the fact that PDT has a favorable adverse event profile and can enhance anti-tumor immune responses as well as demonstrating minimally invasive characteristics, it is disappointing that PDT is not broadly utilized in the clinical setting for the treatment of malignant and/or non-malignant diseases. Several issues still hinder the development of PDT, such as those related with light, tissue oxygenation and inherent properties of the photosensitizers. Various photosensitizers have been designed/synthesized in order to overcome the limitations. In this Review, we provide a general overview of the mechanisms of action in terms of PDT in cancer, including the effects on immune system and vasculature as well as mechanisms related with tumor cell destruction. We will also briefly mention the application of PDT for non-malignant diseases. The current limitations of PDT utilization in cancer will be reviewed, since identifying problems associated with design/synthesis of photosensitizers as well as application of light and tissue oxygenation might pave the way for more effective PDT approaches. Furthermore, novel promising approaches to improve outcome in PDT such as selectivity, bioengineering, subcellular/organelle targeting, etc. will also be discussed in detail, since the potential of pioneering and exceptional approaches that aim to overcome the limitations and reveal the full potential of PDT in terms of clinical translation are undoubtedly exciting. A better understanding of novel concepts in the field (e.g. enhanced, two-stage, fractional PDT) will most likely prove to be very useful for pursuing and improving effective PDT strategies.